Analisis Perbandingan Kinerja Jaringan WLAN 2,4 Ghz Dan 5 Ghz Pada Proses Tethering Menggunakan Metode QOS - Slameto, Andika Agus; Khozinul Asror, Muhammad (Jurnal PROCESSOR, 2023)
Currently, the use of Internet technology is overgrowing. With the current pandemic conditions, a student or worker must carry out activities remotely using the internet network, especially the Wireless Local Area Network (WLAN) network. This research describes the performance comparison of a WLAN network using 2.4 GHz and 5 GHz frequencies in the tethering process on smartphones. Determining the performance of a WLAN network that works at 2.4 GHz and 5 GHz frequencies will be focusing of this study. The study of literature, the internet, and observation for data collection is the method used in this study. Quality of Service (QOS) measures the performance of the two WLAN networks with parameters including throughput, packet loss, and delay values. This network performance test was carried out using scenarios in urban and rural areas in the WLAN network tethering process with a frequency of 2.4 GHz and 5 GHz. This wireless LAN network comparison analysis process uses Wireshark supporting software to maximize measurement. The results of measurements using the QOS parameter are then analyzed, and whether the category of good or bad wireless LAN network performance quality uses the TIPHON standard is known.